Positive electrode-solid electrolyte integrated structure and preparation method and application thereof

Through the preparation method of the integrated structure of the positive electrode-solid electrolyte, the interface problem between the positive electrode and the solid electrolyte in solid lithium-ion batteries is solved, and efficient lithium ion transmission and good interface compatibility are achieved, which is suitable for large-scale industrial applications.

CN119673971APending Publication Date: 2025-03-21ZHEJIANG FUNLITHIUM NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411585633.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Interface problems between the positive electrode and the solid electrolyte in solid-state lithium-ion batteries lead to high interfacial impedance and low lithium ion transmission efficiency, and the prior art preparation methods are complex and not suitable for large-scale industrial applications.

Method used

A method of preparing a positive electrode-solid electrolyte integrated structure is adopted to obtain a positive electrode material precursor by ball milling, coated and dried, and stacked with a polymer electrolyte membrane, and hot rolling is carried out at the softening temperature of the polymer electrolyte membrane to form a positive electrode-solid electrolyte integrated structure with gradient distribution of ionic conductive agent.

Benefits of technology

The compatibility between the positive electrode and the solid electrolyte interface is improved, the interface impedance is reduced, the transmission efficiency of lithium ions is improved, and the preparation method is simple and easy to be used in industrial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673971A_ABST
    Figure CN119673971A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode-solid electrolyte integrated structure and a preparation method and application thereof, and the preparation method of the positive electrode-solid electrolyte integrated structure comprises the following steps: S1, adding a positive electrode active material, a conductive agent, a binder and an organic solvent into a ball milling tank, and carrying out ball milling to obtain a positive electrode material precursor; s2, coating and drying the positive electrode material precursor to obtain a positive electrode plate; s3, adding a polymer component, a lithium salt component and a plasticizer component into a stirring tank, and heating and stirring to prepare slurry; s4, pouring the slurry into a material box, carrying out tape casting by using a tape casting machine, and cooling and solidifying the slurry to obtain a polymer electrolyte membrane; s5, stacking the positive plate in the step S2 and the polymer electrolyte membrane in the step S4, and performing hot rolling at the softening temperature of the polymer electrolyte membrane to obtain a positive electrode-solid electrolyte integrated structure; the preparation method has the advantages of simple synthesis and more excellent cycle performance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a positive electrode-solid electrolyte integrated structure and a preparation method and application thereof. Background Art

[0002] In recent years, solid-state lithium-ion batteries have received extensive attention and attention due to their higher safety and energy density. However, ionic conductivity and interface problems are still the two main difficulties that lithium-ion batteries need to overcome, especially the solid-solid interface problem, which seriously hinders the practical application and development of solid-state lithium-ion batteries, among which the interface problem on the positive electrode side is more prominent.

[0003] The interface between the cathode and the solid electrolyte faces several major problems. First, poor physical contact leads to high interfacial impedance and low lithium ion transfer efficiency. As the number of cycles increases, the volume expansion and contraction of the cathode material will cause physical stratification. Secondly, the inherent electrochemical instability between the cathode and the solid electrolyte interface, complex side reactions will significantly reduce the interfacial compatibility, and the side reaction products formed after the solid electrolyte reaction will greatly increase the impedance of the battery.

[0004] In order to achieve good compatibility between the electrode and the solid electrolyte interface, researchers have proposed a variety of solutions, such as composite cathode preparation, cathode particle coating modification, etc., as follows:

[0005] 1. The solid positive electrode composite material, its preparation method and application disclosed in application number CN201810139903.6, uses electrostatic spray technology to spray polymer solution and positive electrode active material dispersion onto an organic three-dimensional network structure, so that the positive electrode active material and electrolyte salt are distributed in the pores contained in the continuous organic phase. These organic fibers can provide a large number of special interface ion transport channels, greatly improving the ion conductivity of the solid positive electrode composite material and reducing the interface impedance. However, the organic three-dimensional network of this patent is prepared by electrospinning. For industrial applications, only about 10% of the electrospinning system is polymer, the spinning efficiency is low, the organic solvent cost is high, it is not suitable for recycling, it is easy to cause environmental pollution, and the cycle performance needs to be improved, so it is not suitable for large-scale industrial applications;

[0006] 2. A porous organic compound electrolyte and its preparation method and application disclosed in application number CN201910231487.7 synthesizes a porous organic cage compound electrolyte, which is composed of a skeleton and an electrolyte salt. The skeleton includes a porous organic compound and anions located on the porous organic compound and capable of splitting the anion-cation pairs of the electrolyte salt. Although the porous organic compound electrolyte can be wrapped on the surface of the positive electrode particles to increase the contact area between the solid electrolyte and the positive electrode active material, and the porous structure is conducive to the relief of stress in the positive electrode during the charge and discharge process, and the good solubility greatly improves the processing performance of the all-solid-state positive electrode, the synthesis of the porous organic cage compound requires complex equipment, complex steps and a long cycle, which is not conducive to industrial application;

[0007] 3. Application No. CN201710486842.6 discloses a lithium-ion battery ternary positive electrode gradient distribution material precursor and its application. The gradient distribution material precursor is Ni 0.6 Co 0.2 Mn 0.2 (OH)2, which gradually reduces the Ni content from the core layer, increases the Co and Mn content, and forms a layer similar to 1:1:1 in the outermost layer; the obtained gradient distribution material has its own unique function under high voltage, has a high specific capacity, and has excellent cycle stability at small or large rates. However, the positive electrode gradient distribution design only performs element gradient design for the positive electrode material, and performs gradient design of each battery component based on the battery structure.

[0008] Particle coating and composite materials usually have poor cycle performance and are accompanied by a complicated preparation process. In addition, the current positive electrode gradient design only targets the positive electrode material itself, which is limited to the positive electrode side and does not truly achieve the synergy between the positive electrode side and the electrolyte. Therefore, it is very important to invent a solid-state gradient positive electrode that is simple to synthesize and has better cycle performance and stability. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a positive electrode-solid electrolyte integrated structure and a preparation method and application thereof, which is simple to synthesize and has better cycle performance and stability.

[0010] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a positive electrode-solid electrolyte integrated structure, comprising the following steps:

[0011] S1, adding a positive electrode active material, a conductive agent, a binder and an organic solvent into a ball mill, and performing ball milling to obtain a positive electrode material precursor;

[0012] S2, the positive electrode material precursor is coated and dried to obtain a positive electrode sheet;

[0013] S3, adding the polymer component, the lithium salt component, and the plasticizer component into a stirring tank, heating and stirring to form a slurry;

[0014] S4, pouring the slurry into a material box, using a tape casting machine to cast the slurry, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0015] S5, stacking the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together and hot rolling them at the softening temperature of the polymer electrolyte membrane to obtain a positive electrode-solid electrolyte integrated structure.

[0016] Preferably, in step S1, the positive electrode active material is one of LiFePO4, NCM811, NCM622, and NCM523, the conductive agent is one of conductive carbon black (Super P), acetylene black (AB), and Ketjen black (KB), the binder is one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), and polyacrylic acid (PAA), and the organic solvent is one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).

[0017] Preferably, in step S3, the polymer component includes one or at least two combinations of polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polypyrrole (PPy), polyaniline (PANI), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polypropylene oxide (PEO), polyvinylidene chloride (PVDC) and their derivatives; the lithium salt component includes one or at least two combinations of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium tetrafluoroarsenate (LiAsF4), lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB). The plasticizer component includes a solid plasticizer and a functional plasticizer, the solid plasticizer component is one or a combination of at least two of ethylene carbonate (EC), cyclopentane sulfone (TMS), and succinonitrile (SN), and the functional plasticizer component is one or a combination of at least two of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,2-dimethoxypropane (DMP), dimethoxymethane (DMM), ethylene glycol dimethyl ether (DME), acetonitrile (ACN), trimethyl phosphate (TMP), triethyl phosphate (TEP), fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), and 1,3-propylene sultone (PST).

[0018] Preferably, in step S3, the polymer component and the lithium salt component account for 15-35% of the total mass of the slurry, the polymer component accounts for 35-70% of the total mass of the polymer component and the lithium salt component, the plasticizer component accounts for 65-85% of the total mass, and the solid plasticizer accounts for 85-95% of the plasticizer component.

[0019] Preferably, the polymer component and the lithium salt component account for 20-30% of the total mass of the slurry, the polymer component accounts for 50-65% of the total mass of the polymer component and the lithium salt component, the plasticizer component accounts for 70-80% of the total mass, and the solid plasticizer accounts for 89-92% of the plasticizer component.

[0020] Preferably, in step S3, the stirring speed is 100-2000 rpm, the stirring temperature is 60-150° C., and the stirring time is 30-180 min.

[0021] Preferably, in step S4, the scraper gap of the tape casting is controlled to be 100 to 400 μm, the tape speed is 0.05 to 0.5 m / min, and natural cooling or semiconductor cooling is performed after the tape casting, and the semiconductor cooling setting temperature is -10 to 10°C.

[0022] Preferably, in step S5, the hot rolling speed is 0.05-1 m / min, the rolling temperature is 90-140° C., and the reduction ratio is 10-80%.

[0023] And a positive electrode-solid electrolyte integrated structure, which is prepared by the preparation method of the positive electrode-solid electrolyte integrated structure.

[0024] And a solid-state lithium-ion battery, comprising the above-mentioned positive electrode-solid electrolyte integrated structure.

[0025] Compared with the prior art, the advantages of the present invention are:

[0026] 1. The polymer electrolyte membrane in the technical solution has a thermal softening property. The softening of the polymer electrolyte membrane is controlled by adjusting the roller temperature. Then the positive electrode sheet and the polymer electrolyte membrane are stacked and simply hot rolled to achieve penetration between the components. The positive electrode active material and the polymer component can be in close contact to form a positive electrode-solid electrolyte integrated structure with a gradient distribution of the ion conductive agent, which can greatly improve the interface compatibility problem and has good stability.

[0027] 2. One side of the integrated structure has more ion-conductive polymers, which can be in smooth and close contact with the polymer electrolyte membrane and provide a channel for the rapid transmission of lithium ions. The other side of the integrated structure has more electronic conductive agents, which can provide rapid electron transmission as a current collector, with low impedance, and can achieve better battery cycle performance;

[0028] 3. This preparation method is simple to operate and easy to implement. It can simply and quickly produce a positive electrode-solid electrolyte integrated structure with a gradient distribution of ion conductive agent, and is suitable for large-scale continuous production and preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a structural schematic diagram of the cathode-solid electrolyte integrated structure in the present invention;

[0030] Figure 2 Schematic diagram of the cycle performance of button batteries composed of Example 1 and Comparative Example 1;

[0031] Figure 3 Schematic diagram of the cycle performance of button batteries composed of Example 3 and Comparative Example 3. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below with reference to the accompanying drawings.

[0033] Example:

[0034] A method for preparing a positive electrode-solid electrolyte integrated structure comprises the following steps:

[0035] S1, adding a positive electrode active material, a conductive agent, a binder and an organic solvent into a ball mill, and performing ball milling to obtain a positive electrode material precursor;

[0036] S2, the positive electrode material precursor is coated and dried to obtain a positive electrode sheet;

[0037] S3, adding the polymer component, the lithium salt component, and the plasticizer component into a stirring tank, heating and stirring at a stirring speed of 100 to 2000 rpm, a stirring temperature of 60 to 150° C., and a stirring time of 30 to 180 min to prepare a slurry;

[0038] S4, pouring the slurry into a material box, using a tape casting machine to cast, the scraper gap is controlled to be 100-400 μm, the tape speed is 0.05-0.5 m / min, and after the tape casting, natural cooling or semiconductor cooling is performed, and the slurry is cooled and solidified to obtain a polymer electrolyte membrane;

[0039] S5, stacking the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together and hot rolling them at the softening temperature of the polymer electrolyte membrane, with a hot rolling speed of 0.05-1 m / min, a rolling temperature of 90-140° C., and a reduction rate of 10-80%, to obtain a positive electrode-solid electrolyte integrated structure (see Figure 1 ).

[0040] In step S1, the positive electrode active material is one of LiFePO4, NCM811, NCM622, and NCM523, the conductive agent is one of conductive carbon black (Super P), acetylene black (AB), and Ketjen black (KB), the binder is one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), and polyacrylic acid (PAA), and the organic solvent is one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).

[0041] In step S3, the polymer component includes one or a combination of at least two of polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polypyrrole (PPy), polyaniline (PANI), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polypropylene oxide (PEO), polyvinylidene chloride (PVDC) and their derivatives, wherein the single component is preferably PEO and PAN, and the multi-component is preferably PVDF / PEO and PAN / PEO. When the polymer component is a combination of at least two, the main polymer accounts for 50-95% of the total mass of the polymer component, preferably 65-85%.

[0042] In step S3, the lithium salt component includes one or a combination of at least two of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium tetrafluoroarsenate (LiAsF4), lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB), wherein the lithium salt component is preferably LiDFOB, LiPF6 and LiClO4.

[0043] In step S3, the plasticizer component includes a solid plasticizer and a functional plasticizer, the solid plasticizer component is one or a combination of at least two of ethylene carbonate (EC), cyclopentane sulfone (TMS), and succinonitrile (SN), and the functional plasticizer component is one or a combination of at least two of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,2-dimethoxypropane (DMP), dimethoxymethane (DMM), ethylene glycol dimethyl ether (DME), acetonitrile (ACN), trimethyl phosphate (TMP), triethyl phosphate (TEP), fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), and 1,3-propylene sultone (PST), wherein the functional plasticizer is preferably PC / TMP, VC / FEC, and the ratio is preferably 2:1.

[0044] Furthermore, in step S3, the polymer component and the lithium salt component account for 15-35% of the total mass of the slurry, preferably 20-30%; the polymer component accounts for 35-70% of the total mass of the polymer component and the lithium salt component, preferably 50-65%; the plasticizer component accounts for 65-85% of the total mass, preferably 70-80%; the solid plasticizer accounts for 85-95% of the plasticizer component, preferably 89-92%.

[0045] In step S4, the temperature of the material box is kept consistent with the stirring temperature, the scraper gap is preferably 300 μm, the tape speed is preferably 0.2 m / min, and when semiconductor cooling is used, the semiconductor cooling setting temperature is -10 to 10°C. The cooling method and cooling temperature are matched with the tape speed to ensure that the slurry solidifies into a film before winding. Natural cooling is preferred.

[0046] Embodiment 1,

[0047] A method for preparing a positive electrode-solid electrolyte integrated structure comprises the following steps:

[0048] S1, NCM811, Super P and PVDF were added into a ball milling jar at a mass ratio of 8:1:1, and NMP solvent was added at a solid content of 70%, and the positive electrode material precursor was obtained by ball milling, wherein the ball milling speed was 300 rpm and the ball milling time was 1 h;

[0049] S2, the positive electrode material precursor is coated on aluminum foil and dried to obtain a positive electrode sheet;

[0050] S3, adding PAN, PEO, LiBF4, EC, and ACN in a mass ratio of 14:3:14:61:8 into a stirring tank, heating and stirring at a stirring speed of 1000 rpm, a stirring temperature of 130°C, and a stirring time of 120 min to prepare a slurry;

[0051] S4, pouring the slurry into a material box at 130°C, using a tape casting machine for tape casting, controlling the scraper gap to be 300 μm, and the tape speed to be 0.5 m / min, and cooling naturally after tape casting, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0052] S5. Stack the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together, with the side of the positive electrode sheet away from the aluminum foil overlapping the polymer electrolyte membrane, and then perform hot rolling at a speed of 0.54 m / min, a rolling temperature of 100° C., and a reduction rate of 60% to obtain a positive electrode-solid electrolyte integrated structure.

[0053] Embodiment 2,

[0054] A method for preparing a positive electrode-solid electrolyte integrated structure comprises the following steps:

[0055] S1, NCM811, Super P and PVDF were added into a ball milling jar at a mass ratio of 8:1:1, and NMP solvent was added at a solid content of 70%, and the positive electrode material precursor was obtained by ball milling, wherein the ball milling speed was 300 rpm and the ball milling time was 1 h;

[0056] S2, the positive electrode material precursor is coated on aluminum foil and dried to obtain a positive electrode sheet;

[0057] S3, PEO, PVDF, LiDFOB, EC, ACN were added into a stirring tank in a mass ratio of 10:6:12:60:12, and heated and stirred at a stirring speed of 900 rpm, a stirring temperature of 80°C, and a stirring time of 30 min to form a slurry;

[0058] S4, pouring the slurry into a material box at 80°C, using a tape casting machine for tape casting, controlling the scraper gap to be 300 μm, and the tape speed to be 0.5 m / min, and cooling naturally after tape casting, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0059] S5. Stack the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together, with the side of the positive electrode sheet away from the aluminum foil overlapping the polymer electrolyte membrane, and then perform hot rolling at a speed of 0.5 m / min, a rolling temperature of 90°C, and a reduction rate of 60% to obtain a positive electrode-solid electrolyte integrated structure.

[0060] Embodiment 3,

[0061] A method for preparing a positive electrode-solid electrolyte integrated structure comprises the following steps:

[0062] S1. LiFePO4, Super P and PVDF were added into a ball mill at a mass ratio of 8:1:1, and NMP solvent was added at a solid content of 80%, and the positive electrode material precursor was obtained by ball milling, wherein the ball milling speed was 300 rpm and the ball milling time was 1 h;

[0063] S2, the positive electrode material precursor is coated on aluminum foil and dried to obtain a positive electrode sheet;

[0064] S3, adding PAN, LiPF6, TMS, PC, and TMP in a mass ratio of 10:8:60:10:12 into a stirring tank, heating and stirring at a stirring speed of 1000 rpm, a stirring temperature of 140°C, and a stirring time of 120 min to prepare a slurry;

[0065] S4, pouring the slurry into a material box at 140°C, using a tape casting machine for tape casting, controlling the scraper gap to be 300 μm, and the tape speed to be 0.5 m / min, and cooling naturally after tape casting, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0066] S5. Stack the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together, with the side of the positive electrode sheet away from the aluminum foil overlapping the polymer electrolyte membrane, and then perform hot rolling at a speed of 0.5 m / min, a rolling temperature of 140° C., and a reduction rate of 60% to obtain a positive electrode-solid electrolyte integrated structure.

[0067] Embodiment 4,

[0068] The rest is the same as in Example 1, except that the reduction ratio is 10%.

[0069] Embodiment 5,

[0070] The rest is the same as in Example 1, except that the reduction ratio is 80%.

[0071] Embodiment 6,

[0072] The rest is the same as in Example 1, except that the reduction ratio is 90%.

[0073] Comparative Example 1

[0074] A method for preparing a positive electrode and a solid electrolyte comprises the following steps:

[0075] S1, NCM811, Super P and PVDF were added into a ball milling jar at a mass ratio of 8:1:1, and NMP solvent was added at a solid content of 70%, and the positive electrode material precursor was obtained by ball milling, wherein the ball milling speed was 300 rpm and the ball milling time was 1 h;

[0076] S2, the positive electrode material precursor is coated on aluminum foil and dried to obtain a positive electrode sheet;

[0077] S3, adding PAN, PEO, LiBF4, EC, and ACN in a mass ratio of 14:3:14:61:8 into a stirring tank, heating and stirring at a stirring speed of 1000 rpm, a stirring temperature of 130°C, and a stirring time of 120 min to prepare a slurry;

[0078] S4, pouring the slurry into a material box at 130°C, using a tape casting machine for tape casting, controlling the scraper gap to be 300 μm, and the tape speed to be 0.5 m / min, and cooling naturally after tape casting, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0079] S5, bonding the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together according to a conventional installation process.

[0080] Comparative Example 2

[0081] A method for preparing a positive electrode and a solid electrolyte comprises the following steps:

[0082] S1, NCM811, Super P and PVDF were added into a ball milling jar at a mass ratio of 8:1:1, and NMP solvent was added at a solid content of 70%, and the positive electrode material precursor was obtained by ball milling, wherein the ball milling speed was 300 rpm and the ball milling time was 1 h;

[0083] S2, the positive electrode material precursor is coated on aluminum foil and dried to obtain a positive electrode sheet;

[0084] S3, PEO, PVDF, LiDFOB, EC, ACN were added into a stirring tank in a mass ratio of 10:6:12:60:12, and heated and stirred at a stirring speed of 900 rpm, a stirring temperature of 80°C, and a stirring time of 30 min to form a slurry;

[0085] S4, pouring the slurry into a material box at 80°C, using a tape casting machine for tape casting, controlling the scraper gap to be 300 μm, and the tape speed to be 0.5 m / min, and cooling naturally after tape casting, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0086] S5, bonding the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together according to a conventional installation process.

[0087] Comparative Example 3

[0088] A method for preparing a positive electrode and a solid electrolyte comprises the following steps:

[0089] S1. LiFePO4, Super P and PVDF were added into a ball mill at a mass ratio of 8:1:1, and NMP solvent was added at a solid content of 80%, and the positive electrode material precursor was obtained by ball milling, wherein the ball milling speed was 300 rpm and the ball milling time was 1 h;

[0090] S2, the positive electrode material precursor is coated on aluminum foil and dried to obtain a positive electrode sheet;

[0091] S3, adding PAN, LiPF6, TMS, PC, and TMP in a mass ratio of 10:8:60:10:12 into a stirring tank, heating and stirring at a stirring speed of 1000 rpm, a stirring temperature of 140°C, and a stirring time of 120 min to prepare a slurry;

[0092] S4, pouring the slurry into a material box at 140°C, using a tape casting machine for tape casting, controlling the scraper gap to be 300 μm, and the tape speed to be 0.5 m / min, and cooling naturally after tape casting, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified;

[0093] S5. Laminating the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together according to a conventional installation process.

[0094] The positive electrode-solid electrolyte integrated structure prepared in Examples 1-6 and the positive electrode and solid electrolyte prepared in Comparative Examples 1-3 were respectively installed with lithium sheets into button batteries. All button batteries were subjected to charge and discharge cycle tests. The test environment was 25°C, the voltage test range was 3.0V to 4.35V, the charge rate was 0.2C, the discharge rate was 1.0C, and the number of cycles when the capacity retention rate was reduced to 90% was recorded. The test data is as follows:

[0095]

[0096]

[0097] According to Examples 1-3, Comparative Examples 1-3 and Figure 2-3 It can be seen that by stacking the positive electrode sheet and the polymer electrolyte membrane and performing simple hot rolling, the penetration between the components can be achieved, and the positive electrode active material and the polymer component can be in close contact, forming a positive electrode-solid electrolyte integrated structure with a gradient distribution of the ion conductive agent. Compared with the conventional button battery composed of a positive electrode sheet, a polymer electrolyte membrane and a lithium sheet, the number of cycles can be greatly improved. Taking the capacity retention rate reduced to 90% as an example, it is improved by about 31.2-48.9%.

[0098] According to Examples 1, 4, 5, and 6, different reduction rates have a significant effect on the gradient distribution of the ion conductive agent. If the reduction rate is too high, it is easy to cause cracking of the positive electrode sheet and the polymer electrolyte membrane, which is not conducive to the combination of the two, and the cycle performance cannot be effectively improved. It may also damage the rollers of the roller press, causing irreversible effects on the equipment. If the reduction rate is too low, the positive electrode sheet and the polymer electrolyte membrane cannot be fully combined together, and it is difficult to form an integrated structure with a gradient distribution of the ion conductive agent. It still has a high ohmic impedance and charge transfer impedance, and the cycle performance cannot be effectively improved.

[0099] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode-solid electrolyte integrated structure, characterized in that: The steps include: S1, adding a positive electrode active material, a conductive agent, a binder and an organic solvent into a ball mill, and performing ball milling to obtain a positive electrode material precursor; S2, the positive electrode material precursor is coated and dried to obtain a positive electrode sheet; S3, adding the polymer component, the lithium salt component, and the plasticizer component into a stirring tank, heating and stirring to form a slurry; S4, pouring the slurry into a material box, using a tape casting machine to cast the slurry, and obtaining a polymer electrolyte membrane after the slurry is cooled and solidified; S5, stacking the positive electrode sheet in step S2 and the polymer electrolyte membrane in step S4 together and hot rolling them at the softening temperature of the polymer electrolyte membrane to obtain a positive electrode-solid electrolyte integrated structure.

2. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 1, characterized in that: In the step S1, the positive electrode active material is one of LiFePO4, NCM811, NCM622, and NCM523, the conductive agent is one of conductive carbon black (Super P), acetylene black (AB), and Ketjen black (KB), the binder is one of polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), and polyacrylic acid (PAA), and the organic solvent is one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).

3. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 1, characterized in that: In step S3, the polymer component includes one or a combination of at least two of polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polypyrrole (PPy), polyaniline (PANI), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polypropylene oxide (PEO), polyvinylidene chloride (PVDC) and derivatives thereof; The lithium salt component includes one or a combination of at least two of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium tetrafluoroarsenate (LiAsF4), lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB); The plasticizer component includes a solid plasticizer and a functional plasticizer. The solid plasticizer component is one or a combination of at least two of ethylene carbonate (EC), cyclopentane sulfone (TMS), and succinonitrile (SN). The functional plasticizer component is one or a combination of at least two of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,2-dimethoxypropane (DMP), dimethoxymethane (DMM), ethylene glycol dimethyl ether (DME), acetonitrile (ACN), trimethyl phosphate (TMP), triethyl phosphate (TEP), fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), and 1,3-propylene sultone (PST).

4. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 1, characterized in that: In step S3, the polymer component and the lithium salt component account for 15-35% of the total mass of the slurry, the polymer component accounts for 35-70% of the total mass of the polymer component and the lithium salt component, the plasticizer component accounts for 65-85% of the total mass, and the solid plasticizer accounts for 85-95% of the plasticizer component.

5. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 4, characterized in that: The polymer component and the lithium salt component account for 20-30% of the total mass of the slurry, the polymer component accounts for 50-65% of the total mass of the polymer component and the lithium salt component, the plasticizer component accounts for 70-80% of the total mass, and the solid plasticizer accounts for 89-92% of the plasticizer component.

6. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 1, characterized in that: In step S3, the stirring speed is 100-2000 rpm, the stirring temperature is 60-150° C., and the stirring time is 30-180 min.

7. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 1, characterized in that: In step S4, the scraper gap is controlled to be 100-400 μm during tape casting, the tape speed is 0.05-0.5 m / min, and natural cooling or semiconductor cooling is performed after tape casting, and the semiconductor cooling setting temperature is -10-10°C.

8. The method for preparing a positive electrode-solid electrolyte integrated structure according to claim 1, characterized in that: In the step S5, the hot rolling speed is 0.05-1 m / min, the rolling temperature is 90-140° C., and the reduction ratio is 10-80%.

9. A positive electrode-solid electrolyte integrated structure, characterized in that: The structure is prepared by the method for preparing the positive electrode-solid electrolyte integrated structure according to claims 1 to 8.

10. A solid-state lithium-ion battery, characterized in that: It includes the positive electrode-solid electrolyte integrated structure as described in claim 9.

Citation Information

Patent Citations

  • Lithium ion battery ternary positive electrode gradient distribution material precursor and application thereof

    CN107331858A

  • Solid-state cathode composite material and preparation method thereof, and application of solid-state cathode composite material

    CN110165152A

  • A porous organic compound electrolyte, its preparation method and application

    CN111755735B